Strategi Peningkatan Kualitas Pelayanan Publik pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Melawi - Rikka Septiandini (JPASDEV : Journal of Public Administration and Sociology of Development, 2020)
ABSTRACTThis research aimed to know the quality of service delivery. Assessment of the quality of service delivery is carried out by various institutions, one of which is the Ombudsman. DPMPTSP Melawi Regency is one of the OPD service providers that occupies the red zone in an assessment conducted by the Indonesian Ombudsman of West Kalimantan Province. To know the reason why red report cards on the quality of DPMPTSP Melawi Regency and provide input in the form of strategies to improve service quality, This aimed use qualitative method, using service dimention theory, then analyzed with SWOT analysis and again measured against the theory of service quality improvement strategies. The results of the research show 4 outlines of strategies that can be done by using strengths to take advantage of opportunities, take advantage of opportunities to overcome weaknesses, use strengths to avoid threats, and minimize weaknesses to avoid threats. The resulting strategy is very useful for improving the quality of service delivery in DPMPTSP Melawi Regency.Keywords: Service, Strategy, Strengths, Weaknesses, Opportunities, Threats